Increase in 2.5 Micron Airborne Particulate Matters, AHPCO® and Plasma Nanotechnology in Reducing the Symptoms of Asthma and Allergic Rhinitis - Ghosh, Nabarun; Sigma Xi, MAAAAI; Howard, Aubrey D.; Sherali, Nelofar; Banerjee, Prabir; Bennert, Jeff; Saadeh, Constantine; Revanna, Chandini (European Scientific Journal, ESJ, 2017)
Increase in the particulate matter of size 2.5 microns are a major health concern of the present decade that led to a gradual rise of allergy and asthma cases all over the world. When inhaled, they can reach deep into our lungs and enter tissues via the bloodstream and contribute to health conditions ranging from coughing or lung irritation to chronic bronchitis and cardiovascular complications. These substances are generally composed of the combustion particles, organic compounds and metals. Levels of the most dangerous particles, called PM 2.5 reached beyond the prescribed safe level in all the major cities of the world: Beijing in China, Delhi in India, Los Angeles and New York in the US. PM 2.5 is becoming an ever-increasing problem that must be addressed. We are aiming our research towards the reduction of PM 2.5 in the indoor air by using a novel hybrid technology. The newly developed AHPCO ® or Advanced Hydrated Photocatalytic Oxidation and Plasma Nanotechnology in the Bi-Polar units were tested to evaluate the reduction of the particulate matters with a focus on PM 2.5 as well as animal dander and fungal spores. Utilizing two fiber glass chambers, we analyzed the particle count to assess and evaluate the efficiency of the hybrid AHPCO ® and Plasma Nanotechnology in reducing the particle count present in the indoor air in course of progressive time intervals. The air purification system developed with the novel hybrid technology reduced the indoor particulate matters and animal dander efficiently.